2008
DOI: 10.1139/w08-073
|View full text |Cite
|
Sign up to set email alerts
|

Transposon Tn5281 is the main distributor of the aminoglycoside modifying enzyme gene among isolates of Enterococcus faecalis in Tehran hospitals

Abstract: Infections with high levels of gentamicin-resistant (HLGR) isolates of Enterococcus faecalis are common in Tehran hospitals. Genes encoding such resistance are transmissible by conjugation at high frequency. The purpose of this study was to determine the existence of Tn5281 and its flanking aminoglycoside modifying enzyme gene aac(6')-aph(2") among 102 HLGR isolates of E. faecalis cultured from patients at three hospitals in Tehran, Iran. These isolates were detected by disks containing 120 microg of gentamici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
2
2
Order By: Relevance
“…However, the prevalence of the ermA gene in the present study was 14%. This finding is in contrast with the findings of former studies, which reported that above 90% of E. faecalis isolates had the ermA gene (44,45). The prevalence rates of the aph(2 )Ia and aac( 6)-Ie genes in the present study were 66% and 40%, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the prevalence of the ermA gene in the present study was 14%. This finding is in contrast with the findings of former studies, which reported that above 90% of E. faecalis isolates had the ermA gene (44,45). The prevalence rates of the aph(2 )Ia and aac( 6)-Ie genes in the present study were 66% and 40%, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Nine types of cluster genes encode vancomycin resistance, among which vanA-vanN. vanA and vanB are the most important and prevalent genes in vancomycin-resistant Enterococcus species (45). Genetic factors such as plasmids, integrons, and transposons contribute to the emergence, transfer and the spread of antimicrobial resistance genes, particularly in Enterococcus species, thereby resulting in treatment failure (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, high-level resistance to gentamicin was observed in 31 % of isolated enterococci. This frequency is lower than the rates reported by Dadfarma (57.4%, 2013) and Feizabadi (65%, 2008) (8,26). In this study, the frequency of HLGR isolates was higher in clinical specimens, which may be due to high consumption of antibiotics in clinics or due to collection of samples from hospitalized patients.…”
Section: Discussioncontrasting
confidence: 72%